2020
DOI: 10.1021/acsbiomaterials.0c01251
|View full text |Cite
|
Sign up to set email alerts
|

Blood Oxygenation Using Fluoropolymer-Based Artificial Lung Membranes

Abstract: Artificial lung (AL) membranes are used for blood oxygenation for patients undergoing open-heart surgery or acute lung failures. Current AL technology employs polypropylene and polymethylpentene membranes. Although effective, these membranes suffer from low biocompatibility, leading to undesired blood coagulation and hemolysis over a long term. In this work, we propose a new generation of AL membranes based on amphiphobic fluoropolymers. We employed poly­(vinylidene-co-hexafluoropropylene), or PVDF-co-HFP, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…However, it is technically difficult to process PTFE polymer into a thin, hollow fiber shape due to its high melt viscosity. Kim et al [50] have shown that other fluoropolymers with better processability, such as PVDF and P(VDF-co-HFP), can be processed into membranes with target pore size.…”
Section: Membranes For Artificial Lungmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it is technically difficult to process PTFE polymer into a thin, hollow fiber shape due to its high melt viscosity. Kim et al [50] have shown that other fluoropolymers with better processability, such as PVDF and P(VDF-co-HFP), can be processed into membranes with target pore size.…”
Section: Membranes For Artificial Lungmentioning
confidence: 99%
“…As the protein adsorption is the first step that initiates both the blood coagulation pathway and the inflammatory response [63], many works have focused on minimizing the protein adsorption onto blood-contacting devices [50,[64][65][66][67]. Generally, proteins bind to a surface via hydrophobic interaction, and hence the hydrophilic modification of a surface effectively lowers the protein adsorption, which in turn improves the hemocompati- As the protein adsorption is the first step that initiates both the blood coagulation pathway and the inflammatory response [63], many works have focused on minimizing the protein adsorption onto blood-contacting devices [50,[64][65][66][67]. Generally, proteins bind to a surface via hydrophobic interaction, and hence the hydrophilic modification of a surface effectively lowers the protein adsorption, which in turn improves the hemocompatibility [62].…”
Section: Blood Compatibility (Hemocompatibility)mentioning
confidence: 99%
See 3 more Smart Citations